2015
DOI: 10.1108/pm-05-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Examining the perception of tenants in sustainable office buildings

Abstract: Purpose – The purpose of this paper is to address two major challenges faced by sustainable building owners: first, address the gap between an occupant’s expectations of sustainable building outcomes and what the building actually provides and second, overcome the lack of user knowledge about sustainability design and operation for a particular with regards to performance. Design/methodology/approach – This study used a focus group appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Based largely on the perception of clients, Love et al (2012) conducted a case study and argued that the lack of incentives can be seen as the main barrier. Kato et al (2009), Armitage et al (2011) and later Jailani et al (2015) relied on perceptions by occupants of office buildings to identify any challenges and issues. Zhang et al (2012) used a survey questionnaire of contractors, architects, project managers and engineers involved in office building constructions and concluded that the major barriers were caused by uncertain governmental policies.…”
Section: Barriers Affecting the Green Transitionmentioning
confidence: 99%
“…Based largely on the perception of clients, Love et al (2012) conducted a case study and argued that the lack of incentives can be seen as the main barrier. Kato et al (2009), Armitage et al (2011) and later Jailani et al (2015) relied on perceptions by occupants of office buildings to identify any challenges and issues. Zhang et al (2012) used a survey questionnaire of contractors, architects, project managers and engineers involved in office building constructions and concluded that the major barriers were caused by uncertain governmental policies.…”
Section: Barriers Affecting the Green Transitionmentioning
confidence: 99%
“…Building Quality Assessment and Condition Surveys are among the building performance evaluation mechanism that consider indoor air quality as one of the parameters to be examined in order to determine how a building affects its occupants' level of health (Izran Sarrazin, 2011). Baird and Thompson (2012), Jailani et al, (2015), Kessler (2010), Pei et al, (2015) stipulate that the indoor air quality is a criteria for sustainable office building that needs to be studied.…”
Section: Indoor Air Qualitymentioning
confidence: 99%
“…Moreover, many researchers also agreed that the overall cost for constructing the green building is higher compare to the conventional building (Aliagha et al, 2013;Asdrubali et al, 2013;Dwaikat & Ali, 2016;Liu et al, 2014;Yu at al., 2015). Thus, it is essential to understand the occupier's perceptions and expectations of sustainable building design and technology incorporated in the building since the social aspect is a major principle of sustainability (Jailani et al, 2015). The good performance evidence showed when the green building is employed will attract another developer either from private or government agencies to invest in the green building project as it creates a lot of benefit not only to the user, client but also to sustain the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…members of the public), rather than limiting the assessment to experts. Including all stakeholders in an evaluative process is valuable in that it provides better data for decision making and increasing occupant satisfaction and property performance (Heitel et al, 2015;Jailani et al, 2015). In its original form, the DQI is a facilitated process, rather than simply a survey.…”
Section: The Design Quality Indicatormentioning
confidence: 99%